2012
DOI: 10.24310/espsiescpsi.v5i2.13296
|View full text |Cite
|
Sign up to set email alerts
|

Liderazgo entre iguales en equipos deportivos: una revisión camino a la integración

Abstract: El estudio del liderazgo deportivo se ha centrado de forma mayoritaria en la figura del entrenador, dando menor importancia al liderazgo ejercido por algunos jugadores entre sus compañeros. Sin embargo el desarrollo diario en el ámbito aplicado nos muestra continuamente la importancia del jugador líder dentro de un equipo deportivo, dada la influencia que tiene sobre los demás jugadores y su repercusión en todos los procesos grupales. Este trabajo ofrece una revisión teórica acerca de las investigaciones reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, it should be noted that the results from this study do not show a positive relationship between the three factors of emotional intelligence and leadership, unlike the results of previous studies, in which a direct and positive relationship was found [ 15 , 16 , 17 , 18 ]. The results of this study can perhaps be explained by its small sample size or the fact that we focused on leadership in general and not on each of the five main factors: empathy, social support, influence of decision making, sport values, and task orientation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that the results from this study do not show a positive relationship between the three factors of emotional intelligence and leadership, unlike the results of previous studies, in which a direct and positive relationship was found [ 15 , 16 , 17 , 18 ]. The results of this study can perhaps be explained by its small sample size or the fact that we focused on leadership in general and not on each of the five main factors: empathy, social support, influence of decision making, sport values, and task orientation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SCAT [ 30 ] analyzes responses to a series of statements about how one feels in a competitive situation through a Likert-type scale. A Cronbach’s alpha = 0.107 was obtained in this study, whereas in other studies, Cronbach’s alpha was = 0.91 [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Algunos autores (Barrow, 1977;Northouse 2009, citados en Marcén-Muñío et al, 2016 definen al liderazgo como un proceso grupal donde un individuo ejerce cierta influencia sobre otros con el fin de alcanzar una meta en común. En este intercambio, existen factores que determinarán el impacto de la influencia en procesos grupales como la comunicación, la cohesión y la motivación (Torrado-Quintela, 2012). El liderazgo se configura, entonces, como un proceso interaccional en el cual participan un/a líder, quienes siguen a ese/a líder y los objetivos establecidos (Bohórquez-Gómez-Millán & Checa-Esquiva, 2020).…”
Section: Introductionunclassified